Pedagogika społeczna i praca socjalna - refleksja nad niedokończonymi dyskursami oraz związkiem dyscyplinarno - profesjonalnymi - Kantowicz, Ewa (Pedagogika Społeczna Nova, 2023)
The development of theory and practice on the border of social pedagogy and social work in Poland and various forms of academic education to the field of social work resulted in a discourse on the possible relationships between social pedagogy and social work as specific fields of theory and practice of social action, whose disciplinary and professional identity is still in the process of development and dynamic changes. The aim of the presented article is to explore the discussions present in the literature on the subject of research on the border of social pedagogy and social work, which emerge specific epistemological and normative problems. Undertaking the discourse on social pedagogy as a “metatheory” of social work as well as social work as a scientific-professional activity, one point to the importance of social pedagogy, which is an important area of theory and practice present in the professional aid activities of social workers and training programs for social work. The exemplifications of theoretical approaches analyzed in the presented text are one of the voices in debate about the relationship between social pedagogy and social work (also on the European ground) and encourage reflection on possible changes in the creation of new paradigms and the separation of social work as parallel to the (social) pedagogy new discipline.